Suportabilidade a afundamentos de tensão em geradores DFIG empregando limitador supercondutor - Oliveira, Flávio Duarte Couto (2016)
In the modern world, the generation of electricity is fundamental to the industrial and economic development of a country. Economic growth coupled with growing environmental awareness has lead to an increased concern about energy sources. Therefore, the use of alternative sources was stimulated. Among these alternative sources, one of the most promising is wind power, which have became a viable and competitive source. Among the technologies of wind generators, one of the most used is the Doubly Fed Induction Generator - DFIG, suitable for operation with variable speed turbines. This technology, DFIG, became widely used by some countries in their electrical systems. As a result, these countries were forced to adopt strict grid interconnection rules. One of the main rules requires that plant stay connected to the grid during voltage sags. Additionally, some codes such as the ones from Germany and Spain, requires reactive power infeed during voltage dips in grids, thus reducing sag’s effect. In this work, a theoretical study is held on the influence of sag in wind energy conversion systems using the DFIG technology. After this, a new solution for increasing the robustness of the turbine during a balanced voltage dip is displayed. The new solution is a device that incorporates superconductors current limiters. The device is analyzed in different configurations and strategies, then it is compared with conventional solutions. The validation was carried out by computer simulation used the PSCAD / EMTDC from Manitoba-HVDC. Simulation results presented a good device performance on increasing the robustness of the DFIG.